Tyrosine kinase domain mutations of EGFR gene in head and neck squamous cell carcinoma - Vatte, Chittibabu (Onco Targets Ther, 2017)
BACKGROUND: Epidermal growth factor receptor (EGFR) is a commonly altered gene that is identified in various cancers, including head and neck squamous cell carcinoma (HNSCC). Therefore, EGFR is a promising molecular marker targeted by monoclonal antibodies and small molecule inhibitors targeting the tyrosine kinase (TK) domain. OBJECTIVE: The objective of this study was to investigate the spectrum of mutations in exons 18, 19, 20, and 21 of the EGFR gene in HNSCC patients. MATERIALS AND METHODS: This retrospective study included 47 confirmed HNSCC cases. Mutations in the TK domain, exons 18, 19, 20, and 21 of the EGFR gene, were detected by Scorpion(®) chemistry and ARMS(®) technologies on Rotor-Gene Q real-time polymerase chain reaction. RESULTS: The tumors exhibited EGFR-TK domain mutations in 57% of cases. Four cases of T790M mutations were reported for the first time among HNSCC patients. Out of the total mutations, L861Q (exon 21), exon 20 insertions and deletions of exon 19 accounted for the majority of mutations (21%, 19%, and 17%, respectively). EGFR mutation status was correlated with the higher grade (P=0.026) and advanced stage (P=0.034) of HNSCC tumors. CONCLUSION: Higher frequency of EGFR-TK domain mutations together with the presence of the T790M mutation suggests that identification of these mutations might streamline the therapy and provide a better prognosis in HNSCC cases.